Factors Related to Compliance in Taking Medication in Tuberculosis Patients in The Work Area of Tanjung Morawa Community Health Center, Deli Serdang Regency in 2024 - Silalahi, Hotnida Estirawaty; Wandra, Toni; Sinaga, Taruli Rohana; Manurung, Kesaktian; Sinaga, Janno (Open Access Health Scientific Journal, 2025)
Background: Tuberculosis (TB) remains one of the main causes of death globally. One of the main challenges in TB control is low compliance with treatment, which is often due to limited patient knowledge. This research aimed to investigate the connection between the level of knowledge among patients and their compliance with TB treatment at the Tanjung Morawa Health Centre in Deli Serdang Regency.Methods: This study employs an analytic quantitative design with a correlational approach and a cross-sectional cut. Data were collected simultaneously for both independent and dependent variables from 68 TB patients in the working area of the Tanjung Morawa Health Centre. A structured questionnaire was used to evaluate the level of knowledge and compliance with treatment. Data were analysed using the Chi-Square test to determine the connection between variables.Results: The research results show that there is no significant relationship between age (p=0.077), gender (p=0.098), level of education (p=0.410), and health officers (p=0.509) with compliance to treatment. However, there are significant relationships between employment (p=0.026), family support (p=0.008), and medication supervision (p=0.005) with compliance to treatment. The variable of medication supervision has the highest Exp(B) value (7.800), indicating that this variable is the most influential factor regarding treatment compliance.Conclusion: The presence of medication supervision and strong family support play an important role in increasing compliance with TB treatment. These findings emphasise the need for a health strategy that strengthens the community's patient supervision system and encourages family involvement to optimise TB treatment outcomes.